2021
DOI: 10.1002/ett.4320
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis for IRS‐aided communication systems with composite fading/shadowing direct link and discrete phase shifts

Abstract: Intelligent reflecting surface (IRS) is an emerging technology and serves as a key component of any smart radio environment. In this article, we consider an IRS that assists communication of a direct link between a single-antenna transmitter and a receiver. It is assumed that a direct link experiences composite fading/shadowing and is modeled by Generalized-K distribution. Moreover, IRS has line-of-sight (LoS) paths, therefore, Rician distribution is used to characterize the fading for these paths. We also con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…71 IRS helps to mitigate the effect of wireless channel fading which in turn makes the network energy efficient and improves the signal strength. In a study, 72 it was demonstrated that an IRS-assisted communication system outperforms other baseline systems even with a small number of discrete phase shifts. IRS is capable of solving the problem of AirComp systems suffering a lot from challenging signal propagation conditions.…”
Section: Aircompmentioning
confidence: 99%
“…71 IRS helps to mitigate the effect of wireless channel fading which in turn makes the network energy efficient and improves the signal strength. In a study, 72 it was demonstrated that an IRS-assisted communication system outperforms other baseline systems even with a small number of discrete phase shifts. IRS is capable of solving the problem of AirComp systems suffering a lot from challenging signal propagation conditions.…”
Section: Aircompmentioning
confidence: 99%
“…2) RIS with Direct link: The work on performance analysis of RIS with direct link that is considered in [27]- [30], [33]- [35] is based on approximating the end-to-end SNR using various approximation methods such as the CLT. As shown in Table I, the channel model in [27]- [30], [34], [35] is considered as Nakagami-m, Rician and Rayleigh fading.…”
Section: A Related Workmentioning
confidence: 99%
“…As shown in Table I, the channel model in [27]- [30], [34], [35] is considered as Nakagami-m, Rician and Rayleigh fading. Waqar [33] considers the Rician and K-fading models. It is worth mentioning that the aforementioned fading models do not accurately capture the composite fading and shadowing that is usually experienced in practical channel models.…”
Section: A Related Workmentioning
confidence: 99%
“…Reconfigurable intelligent surface (RIS) has emerged as a promising research topic for sixth‐generation (6G) wireless communications 1‐4 . RIS changes the behavior of the wireless propagation environment and helps to obtain high‐quality signals at the receiver.…”
Section: Introductionmentioning
confidence: 99%
“…Reconfigurable intelligent surface (RIS) has emerged as a promising research topic for sixth-generation (6G) wireless communications. [1][2][3][4] RIS changes the behavior of the wireless propagation environment and helps to obtain high-quality signals at the receiver. An RIS is fabricated by meta-surfaces and it consists of a planar structure to have the ability to reflect with low-cost passive elements.…”
Section: Introductionmentioning
confidence: 99%